DETERMINAN LITERASI KEUANGAN SYARIAH PADA MAHASISWA UNIVERSITAS SYIAH KUALA - Dias Rahmatullah; Muhammad H Haris Riyaldi (JURNAL ILMIAH MAHASISWA EKONOMI ISLAM, 2022)
This study aims to analyze the influence of the determinants of sharia financial literacy on students Syiah Kuala University. The sample in this study amounted to 100 respondents. This research used stratified random sampling method and analyzed using multiple linear regression model. The results of the study show that simultaneously education, information media, the role of ulama, and the social environment have an influence on sharia financial literacy for active undergraduate students in the 2021/2022 academic year. Partially, education and information media have an effect on Islamic financial literacy. Meanwhile, the role of ulama and the social environment has no effect on sharia financial literacy. The role of scholars and the social environment must continue to be improved so that sharia financial literacy both among students and the community can be improved.